Quality Bird’s Eye Chili Production: a Retrospective - Chatterjee, R.; Chattopadhyay, P. K.; Chongtham, T.; Hnamte, V.; Datta Ray, S. K.; Munsi, P. S. (International Journal of Bio-resource and Stress Management, 2023)
Bird’s eye chili (Capsicum frutescens L) is still a neglected crop which has many similarities with commercial cultivated chili species (Capsicum annum L). Like all other chilies, bird’s eye chili is also rich in β Carotene (pro-vitamin A), ascorbic acid (vitamin C) and contains tocopherol (vitamin E) whose role as a vital antioxidant is well known. Capsaicin (N-varillyl-8-methyl-6-nonera-mide (C18H27NO3) and di-hydro capsaicin contributes 69% to its pungency. Bird’s eye chili grows best at soil pH between 6.0 and 7.0. It thrives in climate with growing season temperature in the range of 18-27oC during the day and 15-18oC during the night. Most bird’s eye chilies are processed to extract the oleoresin for sale to the food and pharmaceutical industries due to its’ high pungency, color and medicinal properties. It is used in the manufacture of curry powder, pickle, curry paste, hot sauces etc. Despite its wide usage, bird’s eye chili is yet to draw considerable attentions from the farming community. In North Eastern India the crop is grown commercially. Dry chilies with high pungency are in demand in the market of the European Union, the United States and Japan. Awareness program to promote bird’s eye chili cultivation is necessary for useful exploitation of the crop.